Requirements for the maintenance of Th1 immunity in vivo following DNA vaccination: a potential immunoregulatory role for CD8+ T cells - Gurunathan, S; Stobie, L; Prussin, C; Sacks, D L; Glaichenhaus, N; Iwasaki, A; Fowell, D J; Locksley, R M; Chang, J T; Wu, C Y; Seder, R A (The Journal of immunology (1950), 2000)
Protective immunity against Leishmania major generated by DNA encoding the LACK (Leishmania homologue of receptor for activated C kinase) Ag has been shown to be more durable than vaccination with LACK protein plus IL-12. One mechanism to account for this may be the selective ability of DNA vaccination to induce CD8+ IFN-gamma-producing T cells. In this regard, we previously reported that depletion of CD8+ T cells in LACK DNA-vaccinated mice abrogated protection when infectious challenge was done 2 wk postvaccination. In this study, we extend these findings to study the mechanism by which CD8+ T cells induced by LACK DNA vaccination mediate both short- and long-term protective immunity against L. major. Mice vaccinated with LACK DNA and depleted of CD8+ T cells at the time of vaccination or infection were unable to control infection when challenge was done 2 or 12 wk postvaccination. Remarkably, it was noted that depletion of CD8+ T cells in LACK DNA-vaccinated mice was associated with a striking decrease in the frequency of LACK-specific CD4+ IFN-gamma-producing T cells both before and after infection. Moreover, data are presented to suggest a mechanism by which CD8+ T cells exert this regulatory role. Taken together, these data provide additional insight into how Th1 cells are generated and sustained in vivo and suggest a potentially novel immunoregulatory role for CD8+ T cells following DNA vaccination.